The Role Of Quality Assurance In Supporting Micro-Credentials In European Education And Training Systems - Fonzo, Concetta; Evangelista, Laura (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
This article explores the evolving landscape of micro-credentials in European Education and Training systems, emphasizing the central role of quality assurance in ensuring their credibility, portability and alignment with societal, personal and labour market needs. Drawing on recent European recommendations and research conducted by INAPP, it examines the structural features of micro-credentials, the challenges posed by their implementation, and the quality frameworks required for their success. It highlights how robust quality assurance mechanisms, both internal and external, are essential for stakeholder trust and the effective integration of micro-credentials into national qualification systems, particularly within the context of the green and digital transitions.